Evaluation of residual humoral immune response against SARS-CoV-2 by a surrogate virus neutralization test (sVNT) 9 months after BNT162b2 primary vaccination. Issue 6 (June 2023) - Pezzati, Laura; Milazzo, Laura; Carrozzo, Giorgia; Kullmann, Cristina; Oreni, Letizia; Beltrami, Martina; Caronni, Stefania; Lai, Alessia; Caberlotto, Livio; Ottomano, Cosimo; Antinori, Spinello; Ridolfo, Anna Lisa
Abstract: The humoral response to SARS-CoV-2 vaccination has shown to be temporary, although may be more prolonged in vaccinated individuals with a history of natural infection. We aimed to study the residual humoral response and the correlation between anti-Receptor Binding Domain (RBD) IgG levels and antibody neutralizing capacity in a population of health care workers (HCWs) after 9 months from COVID-19 vaccination. In this cross-sectional study, plasma samples were screened for anti-RBD IgG using a quantitative method. The neutralizing capacity for each sample was estimated by means of a surrogate virus neutralizing test (sVNT) and results expressed as the percentage of inhibition (%IH) of the interaction between RBD and the angiotensin-converting enzyme. Samples of 274 HCWs (227 SARS-CoV-2 naïve and 47 SARS-CoV-2 experienced) were tested. The median level of anti-RBD IgG was significantly higher in SARS-CoV-2 experienced than in naïve HCWs: 2673.2 AU/mL versus 610.9 AU/mL, respectively ( p <0.001 ). Samples of SARS-CoV-2 experienced subjects also showed higher neutralizing capacity as compared to naïve subjects: median %IH = 81.20% versus 38.55%, respectively; p <0.001 . A quantitative correlation between anti-RBD Ab and inhibition activity levels was observed (Spearman's rho = 0.89, p <0.001 ): the optimal cut-off correlating with high neutralization was estimated to be 1236.1 AU/mL (sensitivity 96.8%, specificity 91.9%; AUC 0.979). Anti-SARS-CoV-2 hybrid immunity elicited by a combination of vaccination and infection confers higher anti-RBD IgG levels and higher neutralizing capacity than vaccination alone, likely providing better protection against COVID-19.